Akuarintar as a Media in Arabic Teaching and Learning for Deaf Towards Sustainable Development Goals (SDGS) 2030 - Nuriyatul Hidayah; Nur Anisah Ridwan; Hanik Mahliatussikah; Moch Wahib Dariyadi; Bendine Bekhoula (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2020)
Indonesia is a country that is familiar and closely related to Arabic. Therefore, learning this language becomes an important thing. This research was aimed to explain the development process and the validity level of Application of Arabic-Indonesian Expression Dictionary for Deaf (Akuarintar) as a media in Arabic teaching and learning for students at SMALB YPTB Malang. This research and development method used the ADDIE model which included Assessment/Analysis, Design, Development, Implementation, and Evaluation. The results of the validity test were the language validation test showed the proportion of 83%. The results of material validation were 89%, while the results of media design validation were 87%, and the results of teacher validation were 87%. The results of the Wilcoxon Rank Tests analysis obtained a significance value of p = 0.001 and z = -3.453, which means that the students score of Arabic learning significantly increased after using the Akuarintar application. So, it can be concluded that Akuarintar is very suitable as a media for teaching and learning Arabic for the deaf.